Functional connectivity in major depression: increased phase synchronization between frontal cortical EEG-source estimates. - Olbrich, S.; Trankner, A.; Chittka, T.; Hegerl, U.; Schonknecht, P. (Psychiatry Res, 2014)
Structural and metabolic alterations in prefrontal brain areas, including the subgenual (SGPFC), medial (MPFC) and dorsolateral prefrontal cortex (DLPFC), have been shown in major depressive disorder (MDD). Still it remains largely unknown how brain connectivity within these regions is altered at the level of neuronal oscillations. Therefore, the goal was to analyze prefrontal electroencephalographic phase synchronization in MDD and its changes after antidepressant treatment. In 60 unmedicated patients and 60 healthy controls (HC), a 15-min resting electroencephalogram (EEG) was recorded in subjects at baseline and in a subgroup of patients after 2 weeks of antidepressant medication. EEG functional connectivity between the SGPFC and the MPFC/DLPFC was assessed with eLORETA (low resolution brain electromagnetic tomography) by means of lagged phase synchronization. At baseline, patients revealed increased prefrontal connectivity at the alpha frequency between the SGPFC and the left DLPFC/MPFC. After treatment, an increased connectivity between the SGPFC and the right DLPFC/MPFC at the beta frequency was found for MDD. A positive correlation was found for baseline beta connectivity and reduction in scores on the Hamilton depression rating scale. MDD is characterized by increased EEG functional connectivity within frontal brain areas. These EEG markers of disturbed neuronal communication might have potential value as biomarkers.
Keywords: Adult; Antidepressive Agents/pharmacology/*therapeutic use; Brain Mapping/methods; *Cortical Synchronization; Depressive Disorder, Major/drug therapy/*physiopathology; Female; Humans; Male; Middle Aged; Nerve Net/drug effects/*physiopathology; Prefrontal Cortex/drug effects/*physiopathology; Rest/*physiology; Treatment Outcome